Prevalence and genotypic characterization of zoonotic intestinal protozoan parasites in transboundary migratory Mongolian Gazelles (Procapra gutturosa): the first survey - Sichao Gao; Bin Hu; Gaojian Li; Xing An; Yanan Xing; Shuyi Han; Yan Chun; Lingling Han; Du Xi; Wenchao Li; Hongxuan He (Parasitology)
The migration of Mongolian gazelles (Procapra gutturosa) poses a potential risk of outbreak for zoonotic intestinal protozoan parasite infections. This study aims to investigate the infection status of zoonotic intestinal protozoan parasites in these migratory Mongolian gazelles. We collected 120 fecal samples from Mongolian gazelles during their migration from Mongolia to China in December 2023. These samples were analysed using amplification and sequencing of partial SSU rRNA genes to detect the 4 presence of zoonotic intestinal protozoan parasites and characterize their genotypes. Our analysis revealed the presence of several zoonotic intestinal protozoan parasites in the sampled Mongolian gazelles. Cryptosporidium spp. was detected in 14.17% (17/120) of the samples, followed by Cystoisospora belli in 13.33% (16/120), Blastocystis sp. in 16.67% (20/120) and Cyclospora cayetanensis in 30.00% (36/120). Moreover, we identified novel host-adapted genotypes of Cryptosporidium spp. and C. belli, as well as the presence of ST2 and ST13 Blastocystis sp. subtypes, while distinct genotypes were found in Blastocystis sp. and C. cayetanensis. This study revealed the status of 4 prevalent zoonotic intestinal protozoan parasite infections in Mongolian gazelles and provided crucial insights into their characteristics. The prevalence of these parasites in the population highlights the potential risk of cross-border transmission of infectious diseases associated with long-distance migration. Furthermore, the identification of novel genotypes contributes to our understanding of the genetic diversity and adaptation of these parasites. These findings can inform the development of protective measures to mitigate the impact of these infections on the health and survival of Mongolian gazelles.